An alternative interpretation of Plato’s view on poetry: Plato’s solutions to the poetic crisis in the 5th century - Macua Martínez, M.ª Elena (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2014)
This essay revises Plato’s views on poetry in the light of the middle 5th- century’s deep crisis that the traditional poetic model was going through. Poets of that period either remain loyal to the traditional model based upon the transcendence and substance of language at the expense of excluding human experience and its uncomfortable complexity in their poems; or else they assume a technical view of language which leads to a more analytical and pragmatic poetry solely linked to the private realm. In this context we have to place Plato’s views on poetry, which may then be understood as a series of personal attempts to fi nd a solution to the crisis thus, he vindicates the traditional ‘enthusiastic’ model, and deprecates the technical poetry, and goes as far as to the worrying synthesis of the Laws in the fi gure of the legislator-poet.